Review of traditional soy-based fermented foods from Indonesia - Tri Nurmaseli; Boby Pranata; Harumi Sujatmiko; Dwi Indah Permata Sari; Ina Permata Sari; Onne Akbar Nur Ichsan (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
Traditional Indonesian soy-based fermented foods most notably tempeh, oncom (red and black varieties), tauco, and kecap (sweet soy sauce) represent a rich intersection of culinary heritage, microbial ecology, and nutritional innovation. This review synthesizes current knowledge on the production methods, microbial communities, biochemical transformations, and potential health implications of these products. Fermentation by molds (e.g., Rhizopus spp. and other filamentous fungi), bacteria (including Bacillus spp. and lactic acid bacteria), and yeasts drives proteolysis, carbohydrate modification, vitamin biosynthesis, and the breakdown of antinutritional compounds such as phytic acid, leading to improved protein digestibility, increased amino acid availability, and the generation of bioactive peptides and other metabolites with antioxidant, antihypertensive, and immunomodulatory potential. We examine traditional and modernized processing practices, strain-level functionality, and analytical approaches used to characterize metabolite profiles and microbial succession. Critical challenges and gaps are identified: inconsistent product quality, microbial safety concerns (including mycotoxins and opportunistic contaminants), limited strain characterization, and the tension between standardization for scale-up and preservation of local artisanal knowledge. We highlight emerging solutions that control starter cultures, integrate omics (metagenomics, metabolomics), and pilot clinical assessments to substantiate health claims and improve process control while maintaining cultural authenticity. By bringing together ethnographic, microbiological, and biochemical perspectives, this review provides a roadmap for interdisciplinary research and responsible commercialization of Indonesian soy-based fermented foods as nutritious, sustainable ethnic foods. Keywords: fermentation, microorganisms, soy-based, traditional foods